Should I share my ice cream? - Willems, Mo. (New York : Hyperion Books for Children, 2011)
Best friends Gerald and Piggie are complete opposites but still manage to have fun together, but when Gerald takes too long to make an important decision, it may be too late to share with Piggie.
Booklist
Horn Book
School Library Journal
Booklist, October 2011
Horn Book, October 2011
School Library Journal, September 2011
Keywords: Elephants -- Juvenile fiction; Ice cream cones -- Juvenile fiction; Sharing -- Juvenile fiction; Swine -- Juvenile fiction; Elephants -- Fiction; Humorous stories; Ice cream cones -- Fiction; Pigs -- Fiction; Sharing -- Fiction; Elephants -- Fiction; Humorous fiction; Ice cream, ices, etc; Pigs -- Fiction; Sharing -- Fiction; Humorous fiction; Readers (Elementary).